Comparison of the Biofire FilmArray Respiratory Panel, Seegene AnyplexII RV16, and Argene for the detection of respiratory viruses - Chan, Maurice (J Clin Virol, 2018)
BACKGROUND: Respiratory infections are common reasons for hospital admission, and are associated with enormous economic burden due to significant morbidity and mortality. The wide spectrum of microbial agents underlying the pathology renders the diagnosis of respiratory infections challenging. Molecular diagnostics offer an advantage to the current serological and culture-based methods in terms of sensitivity, coverage, hands-on time, and time to results. OBJECTIVES: This study aimed to compare the clinical performance of three commercial kits for respiratory viral detection. STUDY DESIGN: The performance of FilmArray Respiratory Panel, AnyplexII RV16, and Argene was compared using clinical respiratory samples (n = 224, comprising 189 nasopharyngeal swabs in Universal Transport Medium (UTM) and 35 endotracheal aspirates), based on common overlapping targets across the platforms. Influenza A “equivocal” and “no-subtype” samples by FilmArray were further compared to a laboratory-developed Influenza A/B test. RESULTS AND CONCLUSIONS: The overall performance of all three platforms appeared to be comparable with regards to sensitivities (95.8–97.9%) and specificities (96.1–98.0%), detection of coinfections, and distinguishment of influenza from non-influenza cases. “Equivocal” and “no-subtype” samples by FilmArray mostly represented weak Influenza A by laboratory-developed test. Lower respiratory tract samples had comparable final-run success-rates and discordant-rates as compared to UTM. Coronavirus HKU1, which was not targeted by AnyplexII RV16, were detected as OC43. The expected test volume would be the main determinant for the selection of platform. Among the platforms, the FilmArray is the most automated but is of the lowest-throughput and has the highest reagent cost.